Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the roots of the quadratic equation [tex]\(x^2 + 2x - 5 = 0\)[/tex], we need to solve for [tex]\(x\)[/tex]. We can do this best by using the quadratic formula, which is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For the given quadratic equation [tex]\(x^2 + 2x - 5 = 0\)[/tex]:
- [tex]\(a = 1\)[/tex],
- [tex]\(b = 2\)[/tex],
- [tex]\(c = -5\)[/tex].
First, let's calculate the discriminant [tex]\(\Delta\)[/tex]:
[tex]\[ \Delta = b^2 - 4ac = (2)^2 - 4(1)(-5) = 4 + 20 = 24 \][/tex]
Next, we use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-2 \pm \sqrt{24}}{2(1)} = \frac{-2 \pm 2\sqrt{6}}{2} \][/tex]
Simplifying the expression inside the fraction:
[tex]\[ x = \frac{-2 + 2\sqrt{6}}{2} \quad \text{and} \quad x = \frac{-2 - 2\sqrt{6}}{2} \][/tex]
This gives us:
[tex]\[ x = -1 + \sqrt{6} \quad \text{and} \quad x = -1 - \sqrt{6} \][/tex]
Thus, the two roots of the equation [tex]\(x^2 + 2x - 5 = 0\)[/tex] are:
[tex]\[ x = -1 + \sqrt{6} \quad (Option \, D) \quad \text{and} \quad x = -1 - \sqrt{6} \quad (Option \, B) \][/tex]
So the correct choices are:
[tex]\[ B. \quad x = -1 - \sqrt{6} \][/tex]
[tex]\[ D. \quad x = -1 + \sqrt{6} \][/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For the given quadratic equation [tex]\(x^2 + 2x - 5 = 0\)[/tex]:
- [tex]\(a = 1\)[/tex],
- [tex]\(b = 2\)[/tex],
- [tex]\(c = -5\)[/tex].
First, let's calculate the discriminant [tex]\(\Delta\)[/tex]:
[tex]\[ \Delta = b^2 - 4ac = (2)^2 - 4(1)(-5) = 4 + 20 = 24 \][/tex]
Next, we use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-2 \pm \sqrt{24}}{2(1)} = \frac{-2 \pm 2\sqrt{6}}{2} \][/tex]
Simplifying the expression inside the fraction:
[tex]\[ x = \frac{-2 + 2\sqrt{6}}{2} \quad \text{and} \quad x = \frac{-2 - 2\sqrt{6}}{2} \][/tex]
This gives us:
[tex]\[ x = -1 + \sqrt{6} \quad \text{and} \quad x = -1 - \sqrt{6} \][/tex]
Thus, the two roots of the equation [tex]\(x^2 + 2x - 5 = 0\)[/tex] are:
[tex]\[ x = -1 + \sqrt{6} \quad (Option \, D) \quad \text{and} \quad x = -1 - \sqrt{6} \quad (Option \, B) \][/tex]
So the correct choices are:
[tex]\[ B. \quad x = -1 - \sqrt{6} \][/tex]
[tex]\[ D. \quad x = -1 + \sqrt{6} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.